Macroscopic and Mechanically Robust Hollow Carbon Spheres with Superior Oil Adsorption and Light‐to‐Heat Evaporation Properties. (24th May 2016) - Zhou, Jianguo; Sun, Zhenlong; Chen, Mingqi; Wang, Jitong; Qiao, Wenming; Long, Donghui; Ling, Licheng
Abstract : Hollow carbon spheres (HCSs) represent a special class of functional materials, to which intense interest has been paid in the fields of materials science and chemistry. A major problem with these materials is the lack of sufficient particle engineering and mechanical strength for practical applications and the difficulty of up‐scaling. Herein, we report a general, template‐free, phase‐separation approach, in which the liquid–liquid phase‐inversion process and a gas‐foaming process are coupled for the first time, for fast and continuous processing of uniform HCSs. The obtained HCSs have particle sizes on the millimeter scale, and a hierarchical structure with an interpenetrating, open‐porous, carbon shell and huge external voids, therefore permitting rapid transport of molecules into, throughout, and out of the hollow structure. By evenly dispersing the CNTs in the precursor solution, CNT‐reinforced HCSs can be achieved with significantly enhanced mechanical strength, hydrophobicity, and electronic and thermal properties. The resulting CNT‐reinforced HCSs offer a viable route to remove the engine oil from water in a fixed‐bed system. Moreover, these floatable HCSs can receive and convert sunlight to heat at the water–air interface, resulting in a great enhancement in solar evaporation rate compared to conventional bulk heating schemes. Abstract : A template‐free phase‐separation approach, in which a liquid–liquid phase‐inversion process and a gas‐foaming process are coupled for the first time, is demonstrated for the fast and continuous processing of millimeter‐scale hollow carbon spheres (HCSs). The obtained HCSs have a hierarchical structure with a porous carbon shell and huge external voids. They also boast a high mechanical strength, high hydrophobicity, good electronic and thermal properties, high oil adsorption ability, and unique light‐to‐heat evaporation properties.